On the time of minimum ionization in the F2 region - Ezquer, Rodolfo Gerardo (2008)
Using measurements of the critical frequency of F2 region (foF2) the validity of the International Reference Ionosphere model to predict the time of minimum ionization is checked. Data obtained at different ionospheric stations have been considered. The CCIR and URSI options are used to model calculations. For CCIR option the results show that good predictions were obtained for about 40% of the considered cases. For the rest of the considered data, the model predicts the minimum at times earlier than that observed in the measurements. The percentages of good predictions obtained with URSI option are lower than those corresponding to CCIR one.